Goblet and Cross, Casket and Tombstone. Names and Things in the Hidden History of the Time of Troubles - Fjodor Uspenskij; Anna Litvina (Studi Slavistici)
In this work we discuss new attributions of valuable and commemorative objects from the mid-16th to the early decades of the 17th century, namely the tombstone of Aleksandra Saburova, the reliquary of Ivan Chvorostinin, the cross from the Gold Storeroom of the Vladimir-Suzdal’ Preserve Museum, the goblet from the sacristy of the Trinity Monastery of St. Sergius, and letters of Ksenija Godunova. Reconsidering the provenance of these objects through the lens of historical onomastics allows us, in particular, to observe the inner functioning of the complex system of the in-law connections and matrilineal kinship, which simultaneously unites and divides the court elites and the Czar, whilst forming the bridge of continuity between the two eras. For the families of Ivan the Terrible, Godunov and Šujskij, the choice of a name once again becomes the space where purely political tasks, everyday life and personal piety collide and intersect.